High-current cathode and anode spots in gas discharges at moderate and elevated pressures - Akishev, Yu; Karalnik, V; Kochetov, I; Napartovich, A; Trushkin, N (Plasma sources science & technology, 2014)
Physical properties of the high-current density spots (which are not the hot arc spots) formed on the electrodes due to development of electro-dynamical and ionization instabilities in the near-electrode layers are the subjects of this paper. The influence of these spots on homogeneity of the plasma column between the electrodes due to initiation of the discharge constriction is discussed and illustrated by the proper experimental data. The geometrical and gas-dynamic effects stabilizing the formation of the anode and cathode current spots at higher gas pressures are described.